Greatly enhanced thermal conductivity of polyimide composites by polydopamine modification and the 2D-aligned structure. Issue 18 (15th December 2020) - Ding, Dongliang; Shang, Zhihui; Zhang, Xu; Lei, Xingfeng; Liu, Zhenguo; Zhang, Qiuyu; Chen, Yanhui
Abstract: Highly thermally conductive polyimide (PI) composites have great potential application in the heat-resistance electronic packaging field, but the poor interface between the PI matrix and fillers limits their application. Herein, we prepared the polydopamine (PDA) modified hexagonal boron nitride (h-BN@PDA)/polyimide (PI) composites by a simple "vacuum filtration - hot pressing" method. In this composite, the interfacial interaction between the PI matrix and h-BN micro-sheets was greatly enhanced after PDA modification, and a 2D-aligned structure was successfully constructed. In this work, the effect of PDA modification on the thermal conductivity, thermal stability and mechanical properties of PI composites was fully investigated. The thermal conductivity of the h-BN@PDA/PI composites rises as the modified filler increases, and reflects a distinct anisotropy on in-plane and through-plane direction. The highest in-plane thermal conductivity, 3.01 W m −1 K −1, is obtained in the 20 vol% h-BN@PDA modified for 6 h (h-BN@PDA(6h))/PI composite, about 1405% higher than pure PI sample, while its T 10% reaches 525.2 °C, and the tensile strength and Young's modulus are still high, about 38.80 MPa and 8.33 GPa. Our study provides a feasible fabrication technology for the high-performance thermal management materials.